Progressive Refinement of Beamforming Vectors for High-Resolution Limited Feedback. (28th July 2009) - Heath, Robert W.; Wu, Tao; Soong, Anthony C. K.
Abstract : Limited feedback enables the practical use of channel state information in multiuser multiple-input multiple-output (MIMO) wireless communication systems. Using the limited feedback concept, channel state information at the receiver is quantized by choosing a representative element from a codebook known to both the receiver and transmitter. Unfortunately, achieving the high resolution required with multiuser MIMO communication is challenging due to the large number of codebook entries required. This paper proposes to use a progressively scaled local codebook to enable high resolution quantization and reconstruction for multiuser MIMO with zero-forcing precoding. Several local codebook designs are proposed including one based on a ring and one based on mutually unbiased bases; both facilitate efficient implementation. Structure in the local codebooks is used to reduce search complexity in the progressive refinement algorithm. Simulation results illustrate sum rate performance as a function of the number of refinements.